2021
DOI: 10.1186/s13195-021-00784-w
|View full text |Cite
|
Sign up to set email alerts
|

Does insulin resistance influence neurodegeneration in non-diabetic Alzheimer’s subjects?

Abstract: Background Type 2 diabetes is a risk factor for Alzheimer’s disease (AD), and AD brain shows impaired insulin signalling. The role of peripheral insulin resistance on AD aetiopathogenesis in non-diabetic patients is still debated. Here we evaluated the influence of insulin resistance on brain glucose metabolism, grey matter volume and white matter lesions (WMLs) in non-diabetic AD subjects. Methods In total, 130 non-diabetic AD subjects underwent M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 60 publications
0
25
0
1
Order By: Relevance
“…Therefore, insulin resistance may not only be a risk factor for the development of AD but also may serve as a feature that aggravates its pathology [38,49]. A recent study revealed that in non-diabetic AD patients, peripheral insulin resistance was independently associated with reduced hippocampal glucose metabolism and with lower grey matter volume, confirming the hypothesis of insulin resistance impact on AD pathology [56]. Moreover, neuroimaging studies of the brain reported significant correlations between the presence of T2DM, obesity, and/or peripheral insulin resistance with decreased hippocampal volume [67,68].…”
Section: Insulin Resistance and Admentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, insulin resistance may not only be a risk factor for the development of AD but also may serve as a feature that aggravates its pathology [38,49]. A recent study revealed that in non-diabetic AD patients, peripheral insulin resistance was independently associated with reduced hippocampal glucose metabolism and with lower grey matter volume, confirming the hypothesis of insulin resistance impact on AD pathology [56]. Moreover, neuroimaging studies of the brain reported significant correlations between the presence of T2DM, obesity, and/or peripheral insulin resistance with decreased hippocampal volume [67,68].…”
Section: Insulin Resistance and Admentioning
confidence: 92%
“…Interestingly, obesity, diabetes, and cognitive impairment/Alzheimer's disease share in common a core feature that is target-organ insulin resistance [55]. Insulin resistance is defined as reduced tissue responsiveness to the physiological action of insulin [56]. Similarly, brain insulin resistance is an impairment of brain cells to respond to insulin input [57].…”
Section: Malfunction Of Insulin Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that the neuroprotective effects of insulin are due to the regulation of phosphorylated tau levels. An increased level of insulin resistance is also associated with high levels of proinflammatory cytokines which are linked to Aβ depositions in the brains [64]. In diabetes, insulin resistance causes mitochondrial dysfunction, triggering inflammatory response with increased levels of cytokines such as interleukin (Il)-1β, Il-6, Il-8, tumor necrosis factor-alpha (TNF-α), alpha-1-antichymotrypsin (ACT) and C-reactive protein (CRP), the same mechanism being triggered in AD [65].…”
Section: Pharmacological Approaches Able Of Impacting Alzheimer's Disease and Its Progressionmentioning
confidence: 99%
“…Insulin signaling involves the brain to take up glucose and synthesize the insulin-degrading enzyme and is also involved in the degradation of β amyloid. In diabetes, due to the change in insulin signaling, a low synthesis of the enzyme involved in its degradation takes place, thus reducing the process of degradation of β-amyloid with abnormal accumulation in the brain [46,64,104,105]. Insulin and insulin-like growth factor (IGF) are hormones that regulate cell metabolism.…”
Section: Implications Of Restoring Metabolic Health In the Therapy Of Alzheimer's Diseasementioning
confidence: 99%